Soybean - Biomass, Yield and Productivity 2019
DOI: 10.5772/intechopen.81101
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Shoot and Root Growth Responses among Soybean (Glycine max) Genotypes to Drought Stress

Abstract: Drought stress is a major limiting factor in soybean production in South Africa. The development of soybean varieties with enhanced tolerance to soil waterlimited induced stress (WLIS) is one sustainable way to deal with drought. Root traits have shown strong potential for improvement of drought tolerance through breeding. The objectives of this study were to evaluate seedling shoot-and root growth responses under WLIS in order to study root morphology as a mechanism to cope with drought stress and to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Based on this idea, this study examined the root morphology of eight L. siceraria genotypes and investigated the various root traits at different substrate depths and root diameter intervals under a water-deficit condition. For instance, different root-related traits, such as primary root length, number and length of lateral roots, and average root diameter, have been proposed as important traits that contribute to regulating water uptake, which is critical under drought stress (Gorim and Vandenberg, 2017 ; Mwenye et al, 2018 ; Brunel-Saldias et al, 2020 ; Gao et al, 2020 ). In this study, a statistically significant effect of water deficit was reported over all the evaluated root traits.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this idea, this study examined the root morphology of eight L. siceraria genotypes and investigated the various root traits at different substrate depths and root diameter intervals under a water-deficit condition. For instance, different root-related traits, such as primary root length, number and length of lateral roots, and average root diameter, have been proposed as important traits that contribute to regulating water uptake, which is critical under drought stress (Gorim and Vandenberg, 2017 ; Mwenye et al, 2018 ; Brunel-Saldias et al, 2020 ; Gao et al, 2020 ). In this study, a statistically significant effect of water deficit was reported over all the evaluated root traits.…”
Section: Discussionmentioning
confidence: 99%
“…However, these reductions were not statistically significant between cultivars in this study. When the literature is examined, it is seen that there are many studies showing that drought stress reduces stem lengths (Rauf et al 2007;Polania et al 2017;Mwenye et al 2018). Studies show that different results can be obtained depending on the onset time of stress and the application period.…”
Section: Resultsmentioning
confidence: 99%
“…The seedling stage is critical to coping with drought stress. Physiological and morphological characteristics such as MDA content, proline, the water content in leaf, root and stem length provide important data to understand the drought tolerance state of wheat during the seedling stage (Polania et al 2017;Mwenye et al 2018;Chun et al 2018;Dien et al 2019). Food security will rely on improved resistance cultivars to drought (Borlaug 2007;Tester and Langridge 2010;Chapman et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When the substrate contained attapulgite, although S. ringens hybrids still had their root biomass reduced under water restriction, the above ground/root dry weight ratio did not change, due to simultaneous reduction in shoot elongation, possibly providing better equilibrium of plants in case of limited water supply. Enhanced root growth in plants is fundamental to improve substrate water exploration and drought tolerance and there are numerous reports about the importance to enlarge root-to-shoot ratios in order to obtain drought tolerant genotypes and improve yield under water stress in various crops [43][44][45].…”
Section: Salvia Fruticosa Growthmentioning
confidence: 99%